LV SCADA - How to Effectively Manage LV Networks with Limited Topology and Electrical Characteristics Data - Nuno Silva (2015)
This paper describes the main developments of the LV SCADA project and addresses the technical challenges to be tackled when managing LV grids. This project entails the development of technological solutions that contribute for an effective Smart Grid implementation, creating flexible solutions allowing the anticipation of future trends, supporting the introduction of new technical, commercial and regulatory solutions to improve operation efficiency. This paper includes a description of the architecture, main functionalities and control capabilities associated to a new advanced LV SCADA that benefits from the AMI data available, allowing more precise network characterization without requiring widespread real-time information acquisition.